Discontinuing antidepressant medication after mindfulness-based cognitive therapy: a mixed-methods study exploring predictors and outcomes of different discontinuation trajectories, and its facilitators and barriers. Issue 11 (11th November 2020) - Huijbers, Marloes J; Wentink, Carolien; Simons, Esther; Spijker, Jan; Speckens, Anne
Abstract : Objectives: This study aimed to explore predictors and outcomes associated with different trajectories of discontinuing antidepressant medication (ADM), in recurrently depressed individuals after participation in mindfulness-based cognitive therapy (MBCT). Facilitators and barriers of discontinuation were explored qualitatively. Design: Mixed-methods study combining quantitative and qualitative data, drawn from a randomised controlled trial. Setting: Twelve secondary and tertiary psychiatric outpatient clinics in the Netherlands. Participants: Recurrently depressed individuals (N=226) who had been using ADM for at least 6 months and in partial or full remission. Regardless of trial condition, we made post-hoc classifications of patients' actual discontinuation trajectories: full discontinuation (n=82), partial discontinuation (n=34) and no discontinuation (n=110) of ADM within 6 months after baseline. A subset of patients (n=15) and physicians (n=7) were interviewed to examine facilitators and barriers of discontinuation. Interventions: All participants were offered MBCT, which consisted of eight weekly sessions in a group. Primary and secondary outcome measures: Demographic and clinical predictors of successful discontinuation within 6 months, relapse risk within 15 months associated with different discontinuation trajectories, and barriers and facilitators of discontinuation. Results: Of the 128 patients assigned to MBCT with discontinuation, only 68 (53%) fully discontinued ADM within 6 months, and 17 (13%) discontinued partially. Predictors of full discontinuation were female sex, being employed and lower levels of depression. Relapse risk was lower after no discontinuation (45%) or partial discontinuation (38%), compared with full discontinuation (66%) (p=0.02). Facilitators and barriers of discontinuation were clustered within five themes: (1) pre-existing beliefs about depression, medication and tapering; (2) current experience with ADM; (3) life circumstances; (4) clinical support and (5) mindfulness. Conclusions: Discontinuing antidepressants appears to be difficult, stressing the need to support patients and physicians in this process. MBCT may offer one of these forms of support. Trial registration number: ClinicalTrials.gov Registry (NCT00928980 ); post-results.